ANALISIS KESALAHAN PENGGUNAAN EJAAN PADA TEKS ESAI MAHASISWA DIPLOMA 3 PERPAJAKAN SEMESTER 5 UNIVERSITAS RIAU - Kurnia Aldani; Charlina ,; Amira Deani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
His study aims to conduct an in-depth analysis of the use of spelling in essays written byDiploma 3 Taxation students who are in their 5th semester at the University of Riau.The importance of correct spelling cannot be underestimated, as spelling errors cansignificantly affect the reader's understanding of the content and intent of the text. Thisstudy uses a qualitative method with a document analysis approach, in which the essaysproduced by the students serve as the primary objects of analysis. Data collection wascarried out by randomly selecting 44 essays from students in the 5th semester. Theresults of the analysis indicate various types of spelling errors frequently made bystudents, including errors in the use of capital letters, prefixes, suffixes, confixes, andcommas that do not conform to the rules of the Enhanced Spelling System Edition 5(EYD 5). This research is expected to make a significant contribution to efforts toimprove students' writing skills. By increasing awareness of the importance of correctspelling, it is hoped that students will better understand and apply the appropriatewriting rules, thereby producing written works that are not only good in terms ofcontent but also in terms of writing technique.Keyword: Spelling Erros, Essay Text